Nivel de conocimiento y hábitos en salud oral de los adolescentes de la institución educativa Simón Bolívar sede central (2023)
It was observed that the results showed a significant increase in adolescents because they had poor knowledge before the intervention. Therefore, after the educational intervention, the results improved positively, as they had little information about oral care and habits, with the educational talks on oral health being favorably received.